Modification of Salmonella Lipopolysaccharides Prevents the Outer Membrane Penetration of Novobiocin - Nobre, Thatyane M. (Biophys J, 2015)
Small hydrophilic antibiotics traverse the outer membrane of Gram-negative bacteria through porin channels. Large lipophilic agents traverse the outer membrane through its bilayer, containing a majority of lipopolysaccharides in its outer leaflet. Genes controlled by the two-component regulatory system PhoPQ modify lipopolysaccharides. We isolate lipopolysaccharides from isogenic mutants of Salmonella sp., one lacking the modification, the other fully modified. These lipopolysaccharides were reconstituted as monolayers at the air-water interface, and their properties, as well as their interaction with a large lipophilic drug, novobiocin, was studied. X-ray reflectivity showed that the drug penetrated the monolayer of the unmodified lipopolysaccharides reaching the hydrophobic region, but was prevented from this penetration into the modified lipopolysaccharides. Results correlate with behavior of bacterial cells, which become resistant to antibiotics after PhoPQ-regulated modifications. Grazing incidence x-ray diffraction showed that novobiocin produced a striking increase in crystalline coherence length, and the size of the near-crystalline domains.